The secret history of the Five Eyes : the untold story of the international spy network - Kerbaj, Richard (Union Square & Co., 2025)
The Five Eyes--a spy network between the intelligence agencies of the US, UK, Canada, Australia, and New Zealand--has been steeped in secrecy since its official formation in 1956. Yet the Five Eyes' very existence is not legally binding--it functions as a marriage of convenience riddled with distrust, competing intelligence agendas, and a massive imbalance of power that favors the US. Richard Kerbaj draws on interviews with intelligence officials, world leaders, and recently declassified archives to reveal the authoritative but unauthorized stories of the alliance. In bypassing the usual censorship channels, he tells this extraordinary account of the Five Eyes' unlikely cast of characters who played a crucial role in its history, and exposes the network's hidden role in influencing global events that continue to shape our daily lives.